Adsorção de cristal de violeta empregando hidróxido duplo lamelar níquel/índio - Santos, Eduardo Teixeira (2023)
The textile industry can produce about 200 L of liquid effluent for every kilogram of textile fabric manufactured. Between 50-55% of the liquid effluent generated in the textile industry is composed of dyes from the dyeing process, which present a great risk of environmental degradation when not treated properly. Therefore, this work aims to synthesize an adsorbent layered double hydroxide of Nickel and Indium (Ni/In-LDH) with high potential in the adsorption of cationic dye crystal violet (CV), present in aqueous solution and widely used in the textile industry. The adsorbent material was synthesized from the coprecipitation process of indium nitrate and nickel nitrate. The characterization of the adsorbent was performed by XRD, FTIR, SEM-EDS, and BET. The characterization results showed that the adsorbent was synthesized successfully, with a basal spacing (BS) of 0.783 nm and a surface area of 106.07 m2 g -1 . In the adsorption tests, the best operating conditions were pH 8.0, adsorbent dosage of 240 mg L-1 , temperature of 50 °C and potential for use of Ni/In-LDH in processes with high ionic strength. In the kinetics and isotherms of adsorption studies results showed that the material presented a contact time up to equilibrium of 30 min, maximum adsorption capacity Qmax of 589.23 mg g-1 , and maintained about 70-75% of the initial adsorption capacity in three successive cycles of adsorption and regeneration in ethanol. The experimental data presented satisfactory adjustment with the Pseudo first order kinetic model (PFO) and the Liu isothermal model. In the thermodynamic study, the results indicated a spontaneity in the adsorption process, an endothermic process and a mechanism of physisorption of CV in Ni/In-LDH. These results demonstrated that Ni/In-LDH has excellent performance in the removal of CV dye in aqueous solutions and may have a high potential for use and reuse in the textile industry.